Role of Intra- and Extracellular Lipid Signals in Cancer Stemness and Potential Therapeutic Strategy - Hu, Jianming; Zhang, Leyi; Chen, Wuzhen; Shen, Lesang; Jiang, Jingxin; Sun, Shanshan; Chen, Zhigang (Frontiers in Pharmacology, 2021)
Accumulating evidence showed that cancer stem cells (CSCs) play a significant role in cancer initiation, resistance to therapy, recurrence and metastasis. Cancer stem cells possess the ability of self-renewal and can initiate tumor growth and avoid lethal factors through flexible metabolic reprogramming. Abnormal lipid metabolism has been reported to be involved in the cancer stemness and promoted the development of cancer. Lipid metabolism includes lipid uptake, lipolysis, fatty acid oxidation, de novo lipogenesis and lipid desaturation. Abnormal lipid metabolism leads to ferroptosis of CSCs. In this review, we comprehensively summarized the role of intra- and extracellular lipid signals in cancer stemness, and explored the feasibility of using lipid metabolism-related treatment strategies for future cancer.